Statistical Learning Game Application Assets for 5th Grade Elementary School Student - Moniaga, Jurike; Indrianti, Yasinta; ., Sasmoko; Halim, Senly-Anthonius (International Journal of Engineering and Technology, 2018)
Mathematics is often identified with difficult subjects, because most people find it difficult to understand mathematics. On the other hand, games can provoke interest in learning and can improve cognitive and motor skills. The research discusses the development of educational games to help learning mathematics in the theme of statistics in 5th grade elementary school student. This educational game is designed with research methods. The application is designed using UNITY to run the program, Paint tool SAI to draw characters, Dragon bones for animation, Adobe Photoshop to create sprite sheet. The results of this research were tried out to students of an elementary school in Jakarta through working on the questions in the game.Â Â
Keywords: Mathematics; Game Education; Statistics.